Pengembangan Kompetensi Menulis Buku Cerita Anak Bagi Calon Guru Sekolah Dasar - Alia, Dwi; Yulianeta, Yulianeta; Mulyati, Yeti; Apriliya, Seni; Damaianti, Vismaia S.; Anshori, Dadang S.; Nuthihar, Rahmad (SAWERIGADING, 2025)
This study aims to identify the challenges, learning needs, and weaknesses in the intrinsic elements of children’s storybooks written by prospective elementary school teachers. The research employed a mixed methods approach with data collected through questionnaires, interviews, and content analysis. Questionnaires were distributed to 122 students from the Primary School Teacher Education (PGSD) and Islamic Primary School Teacher Education (PGMI) programs to identify challenges and learning needs in writing children’s stories. Interviews were conducted with two lecturers teaching children’s literature to explore their perspectives on students’ difficulties. In addition, a content analysis was carried out on 13 student works, consisting of nine children’s storybooks and four educational books, to examine weaknesses in intrinsic elements. Data were analyzed descriptively through triangulation of survey, interview, and content analysis results. The findings reveal that the main challenges lie in narrative perspective (49.18%), plot development (39.35%), and characterisation (36.89%). In terms of learning needs, students require more training in language use (34.43%) and the development of creative originality (31.15%). The content analysis supports these findings, showing narrative weaknesses such as abrupt resolutions, static characters, and the use of unimaginative and non-contextual language. These results highlight the need for a more contextual, practical, and child-literacy-oriented model of story-writing instruction. AbstrakPenelitian ini bertujuan mengungkap kendala, kebutuhan pembelajaran, dan kelemahan unsur intrinsik dalam karya cerita anak yang ditulis oleh mahasiswa calon guru sekolah dasar. Metode yang digunakan adalah pendekatan campuran (mixed methods) dengan teknik pengumpulan data berupa kuesioner terhadap 122 mahasiswa Program Studi PGSD dan PGMI, wawancara dengan dua dosen pengampu mata kuliah sastra anak, serta analisis isi terhadap 13 karya mahasiswa (9 buku cerita anak dan 4 buku pendidikan). Data dianalisis secara deskriptif melalui triangulasi hasil survei, wawancara, dan analisis karya. Hasil penelitian menunjukkan bahwa kendala utama mahasiswa terletak pada aspek sudut pandang (49,18%), alur cerita (39,35%), dan pengembangan tokoh (36,89%). Dalam hal kebutuhan pembelajaran, mahasiswa memerlukan pelatihan dalam penggunaan bahasa (34,43%) dan pengembangan orisinalitas karya (31,15%). Analisis karya memperkuat temuan survei dengan ditemukannya kelemahan naratif berupa resolusi instan, karakter statis, serta penggunaan bahasa yang kurang imajinatif dan tidak kontekstual. Temuan ini menegaskan perlunya model pembelajaran menulis cerita anak yang lebih kontekstual, praktis, dan berorientasi pada literasi anak.